LA DESPROPORCIONALIDAD DE LAS SANCIONES EN LAS CONTRAVENCIONES DE TRÁNSITO DE PRIMERA CLASE EN EL CÓDIGO ORGÁNICO INTEGRAL PENAL - TOLEDO IÑIGUEZ, TEREZA DE JESUS (2016)
This research includes a study of legal issues related to disproportionality of sanctions on infringements of traffic class in the Code of Criminal Integral. The Constitution of the Republic of Ecuador in article 76 paragraph 6 stable the principle of proportionality, which meant that the penalty to be imposed is not excessive considering the gravity of the act committed and the damage caused, in this research pretend show that the current sanctions that the offender traffic class are imposed are too, which violate the principle of proportionality, and thus is infringing the rights of the offender, as the principle of proportionality necessarily serves to limit the punitive power of the state, preventing exaggerated penalties imposed and thus guarantee the rights of citizens. An important for the realization of this research, reason is the high rate of traffic violations class in Ecuador, as the measures the legislature has taken to combat it have not been appropriate, and to stiffen penalties or increasing penalties is not helping to reduce this problem. The legal issues cited in prefixed paragraphs, is the basis of this research, which shows that existing disproportion between the punishment and the act committed, as by imposing on the offender transit exaggerated penalties, such as imprisonment of three days, fine of a unified basic wage of workers in general and reduction of ten points to the license, for committing a wrongful act of nature, therefore an amendment to the Criminal Code of Integral regarding traffic contraventions consider necessary first class, for it removed the imprisonment and a penalty proportionate to the crime committed, whether the reduction of ten points to the driver's license or a fine of a unified basic wage of workers in general, to put this so protect the rights of the offender and respect the constitutional stipulated.